Self-Identity Through the Prism of Other in Merold Westphal's Existential Philosophy of Religion - Ševčenko, Serhij Ivanovyč (Journal for the study of religions and ideologies, 2019)
For the first time in the Ukrainian religious studies the article overviews the interrelation of the works of Merold Westphal, which reveal the specificity of the correlation of the ideas of S. Kierkegaard and E. Levinas. The peculiarities of S. Kierkegaard`s and E. Levinas` interpretation of the biblical teaching Thou shalt love thy neighbour as thyselfand its rethinking in the existential theology of M. Westphalare analyzed. The dichotomy I - Other is investigated in the context of realization of true Self and the search for the answer to the question that M. Westphalasks himself, which of the ideas will further unite people. It is shown that for E. Levinas it is infinity and ineffability that constitute the radical individual responsibility of each of us for our neighbour. S. Kierkegaard and his pseudonyms, according to M. Westphal, tell about the idea of Eternal, and mainly based on the more expressive Christian idea of true God. It is proven that M. Westphal justified the inadmissibility of the Levinas post-biblical incorporation of religion into ethics, when it is the truth that becomes the criterion of a subject, but not kindness, freedom, sincerity; it is objectivity, not subjectivity. He opposed him the categoricalness of the Kierkegaard`s principle, according to which religion is unconditional prerequisite of ethics.